(untitled) (Journal of the Sociology and Theory of Religion, 2025)
Friedrich Hayek has been a topic of considerable interest, especially among classical-liberal/libertarian scholars and societies. And the studies of Laozi’s philosophy have also drawn increasing attention worldwide. Hayek and another great libertarian philosopher Murray Rothbard also considered that Laozi’s philosophy matched the libertarian principle. Increasingly, classical liberals/libertarians seek answers to current political, economic, and social questions within Laozi’s wisdom from over 2000 years ago and the Spanish scholastic’s teaching since the 16th century. By comparing and integrating the knowledge approach theories of Hayek, Laozi, and Luis de Molina, this paper uncovers new insights into how the integrated version of the above three great philosophers can benefit modern society for peace, prosperity, and liberty.